Pengaruh Ukuran Perusahaan, Return On Equity dan Leverage terhadap Nilai Perusahaan: (Emiten Ritel Bursa Efek Indonesia Periode 2020-2023) - Nanin Pattingalloang; Wastam Wahyu Hidayat; Gilbert Rely (Institut Teknologi dan Bisnis (ITB) Semarang, 2025)
This study aims to examine the factors that affect the company's value. There are several factors used, including company size, return on equity, and leverage. The purpose of this study is to empirically test whether company size, return on equity, and leverage, affect the value of companies in retail issuers on the Indonesia Stock Exchange. This study uses secondary data from the annual financial statements of retail issuers of the Indonesia Stock Exchange (IDX) for the 2020-2023 period. There were 15 issuers that were sampled or as many as 60 observations that met the criteria in the research sample using the purposive sampling method. The analysis methods used are Descriptive Statistical Analysis, Classical Assumption Test, Multiple Linear Regression Test, and Hypothesis Test. The results of the study show that company size, return on equity, and leverage have a significant effect on the value of the company.